2000
DOI: 10.1037/0022-3514.79.2.211
|View full text |Cite
|
Sign up to set email alerts
|

"Mood contagion": The automatic transfer of mood between persons.

Abstract: The current studies aimed to find out whether a nonintentional form of mood contagion exists and which mechanisms can account for it. In these experiments participants who expected to be tested for text comprehension listened to an affectively neutral speech that was spoken in a slightly sad or happy voice. The authors found that (a) the emotional expression induced a congruent mood state in the listeners, (b) inferential accounts to emotional sharing were not easily reconciled with the findings, (c) different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
449
4
14

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 590 publications
(501 citation statements)
references
References 34 publications
19
449
4
14
Order By: Relevance
“…For example, when observing another person experiencing a painful injury and wincing, observers imitate the wince in their own expression [39]. Similarly, participants will mimic postures such as foot shaking and nose rubbing carried out by a person with whom they are conversing [40], and when they repeat another's speech they adopt the other's tone of voice as well [41]. Finally, it has recently been demonstrated that conversational partners dynamically align their posture [42].…”
Section: Resultsmentioning
confidence: 99%
“…For example, when observing another person experiencing a painful injury and wincing, observers imitate the wince in their own expression [39]. Similarly, participants will mimic postures such as foot shaking and nose rubbing carried out by a person with whom they are conversing [40], and when they repeat another's speech they adopt the other's tone of voice as well [41]. Finally, it has recently been demonstrated that conversational partners dynamically align their posture [42].…”
Section: Resultsmentioning
confidence: 99%
“…There is now increasing evidence that one individual's emotion-related bodily movements can at times trigger that emotion in other persons (see Bargh & Chartrand, 1999;and Neumann & Strack, 2000, for a summary of relevant research). The intriguing experiments reported by Neumann and Strack (2000) demonstrated, for example, that a spoken statement whose content was affectively neutral but that was expressed in either a slightly happy or slightly sad tone of voice evoked a congruent affective state in the listeners. Moreover, this contagion occurred even though the listeners had not consciously wanted to share the speaker's emotion, had not devoted much of their cognitive resources to what was said so that they had not fully understood the content, and were unaware that their mood had been affected by the statement's emotional tone.…”
Section: Effects Of Anger-related Muscular Movementsmentioning
confidence: 99%
“…Initially, scholars believed that emotional contagion is caused by interaction partners automatically mimicking each other's facial expressions (Hatfield et al, 1993). However, more recent evidence suggests that facial mimicking is not a necessary condition for emotional contagion to occur (Hess & Blairy, 2001;Neumann & Strack, 2000). Instead, the mere detection of an emotion in another person seems to be sufficient to transfer this emotion to the person who detected the emotion (Neumann & Strack, 2000).…”
Section: Emotional Contagionmentioning
confidence: 99%